Human biomechanics study in knee osteoarthritis (OA) for 3D printed footwear development - Leong, Andy En Li (Nanyang Technological University, 2023)
With knee osteoarthritis (OA) being the most prevalent joint disease amongst the population, there has been a rise in need to tackle this issue and curb the upwards trend. A popular non-invasive solution is the use of orthoses like specialized shoes and custom insoles, and the continuous advancement of 3D printing technology has enabled the manufacturing of such orthoses to be optimized. Nevertheless, as the orthosis needs to be customized to each individual’s foot profile, it is not feasible to manufacture each and every prototype due to the costs involved. As such, there is a need for a simulation model to test designs prior to fabrication which leads to the objective of this study of developing a comprehensive 3D model of the human foot to allow finite element analysis (FEA) to be conducted and to utilize those results to further optimize and develop footwear to delay and prevent knee OA. A 3D Model of left foot model obtained from a single participant was used alongside a custom midsole 3D model designed using Computer Aided Design and imported into a Finite Element Analysis software known as ANSYS to obtain a simulation model and deformation data under load. The results of the simulation model were compared against real-world data and were shown to be accurate within an acceptable range of 5%, thus achieving the objective of a comprehensive simulation model.